The effect of temperature and LiClO4 in the water structure: a Raman spectroscopy study - Pereira Neto,Ana Maria (2004)
A method to obtain the components of the broad Raman band assigned to the OH stretching vibrations of liquid water was developed, by considering the subtraction of spectra at several temperatures. From these subtractions a set of six components, that we denominate "basis", was determined corresponding to several water structures. This procedure fixes the number of components in the fitting as well as the values of the frequencies, generating a set of six gaussian bands from which the water spectrum can be calculated at any temperature. With such bands the spectrum of lithium perchlorate was calculated at several concentrations and temperatures. It was verified that the spectrum so obtained was identical to that of pure water at a higher temperature. The presence of an isosbestic point is a proof of the existence of equilibrium between the several structures. The enthalpy and entropy values were determined for the isosbestic point and for pairs of structures corresponding to the gaussian bands.